2010
DOI: 10.1603/me10111
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Ixodes ricinus (Acari: Ixodidae) Under Challenging Conditions of Temperature and Humidity Is Influenced by Borrelia burgdorferi sensu lato Infection

Abstract: To determine whether Borrelia burgdorferi sensu lato (s.l.) inßuences tick survival under thermohygrometric stress, Ixodes ricinus (L.) (Acari: Ixodidae) questing ticks were tested under various relative humidities (13, 32, 51.5, 61, and 89% RH) at two different temperatures (12.5 and 25ЊC) and investigated for Borrelia infection. Survival rate of females was highest (77.6%), followed by males (51.6%), and nymphs (43.2%). The thermohygrometric factor that most importantly determined survival was saturation de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
94
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(104 citation statements)
references
References 50 publications
4
94
2
1
Order By: Relevance
“…Infection status also did not influence supercooling point. This result is consistent with the research done by Hermann & Gern (2010) who showed that ticks infected with Borrelia are more resistant to inconsistent temperature and humidity environments even though Dermacentor variabilis is a different tick species and has different bacteria species.…”
Section: Discussionsupporting
confidence: 93%
“…Infection status also did not influence supercooling point. This result is consistent with the research done by Hermann & Gern (2010) who showed that ticks infected with Borrelia are more resistant to inconsistent temperature and humidity environments even though Dermacentor variabilis is a different tick species and has different bacteria species.…”
Section: Discussionsupporting
confidence: 93%
“…3. The percentage of high-fat fully hydrated (H&F), low-fat fully hydrated (L&F), and low-fat moderately hydrated (L&M) Ixodes ricinus ticks that walked towards the wet (light grey bars) or the dry end (white bars) of the arena after 2 h. common one (Casati et al 2004;Jouda et al 2004;Morán Cadenas et al 2007;Gern et al 2010;Herrmann and Gern, 2010). B. bavariensis (6·8%), formerly B. garinii OspA serotype 4, a newly described genospecies (Margos et al 2009), is reported for the first time in the area, although it was already described in Switzerland (Staatswald) (Hu et al 2001;Huegli et al 2002;Pérez et al manuscript submitted ).…”
Section: Borrelia Infection In Ticksmentioning
confidence: 99%
“…In the interface of field collected I. ricinus infected by different quantity of representatives of 4 species Borrelia d e t e r m i n e d b y r e a l t i m e P C R a n d RLB a very interesting fact was discovered: the better surviving of adult ticks infected by mean doses of pathogens (Herrmann & Gern, 2010). This phenomenon was a brilliant confirmation of prof. Alekseev (1984) theory that among other criteria of interface specificity in the couple "vectorpathogen" the existence of optimum pathogen doses (mean ones) do exist not only in the pairs "Leishmania-sand flies", plague agent and fleas (Alekseev, 1984), "Tick-borne encephalitis (TBE) virus -Ixodes persulcatus" (Alekseev & Kondrashova, 1985), but in the couple "Borrelia-Ixodes ticks" (Herrmann & Gern, 2010).…”
Section: Ticks Behaviour and Borrelia Transmissionmentioning
confidence: 57%
“…This phenomenon was a brilliant confirmation of prof. Alekseev (1984) theory that among other criteria of interface specificity in the couple "vectorpathogen" the existence of optimum pathogen doses (mean ones) do exist not only in the pairs "Leishmania-sand flies", plague agent and fleas (Alekseev, 1984), "Tick-borne encephalitis (TBE) virus -Ixodes persulcatus" (Alekseev & Kondrashova, 1985), but in the couple "Borrelia-Ixodes ticks" (Herrmann & Gern, 2010).…”
Section: Ticks Behaviour and Borrelia Transmissionmentioning
confidence: 99%